Thank you for registering.

One of our academic counsellors will contact you within 1 working day.

Please check your email for login details.
MY CART (5)

Use Coupon: CART20 and get 20% off on all online Study Material

ITEM
DETAILS
MRP
DISCOUNT
FINAL PRICE
Total Price: Rs.

There are no items in this cart.
Continue Shopping

if cosecA+cotA = p, then prove that cosA = p 2 -1/p 2+1

if cosecA+cotA = p, then prove that cosA = p2-1/p2+1

Grade:10

1 Answers

Arun
25763 Points
4 years ago
Cosec theta + cot theta = P (given) we know, cosec² theta - cot² theta = 1 (cosec theta + cot theta)( cosec theta - cot theta)= 1 (cosec theta - cot theta) × P = 1 ( cosec theta - cot theta) = 1/P Let's solve (i ) and (ii) cosec theta = 1+ P²/2P cot theta = P²-1/2P cot theta / cosec theta= P²-1/2P×2P/P2²+1 cos theta = P²-1/P²+1

Think You Can Provide A Better Answer ?

Provide a better Answer & Earn Cool Goodies See our forum point policy

ASK QUESTION

Get your questions answered by the expert for free